2009
DOI: 10.1002/chem.200802454
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen‐Atom Transfer Reactions from ortho‐Alkoxy‐Substituted Phenols: An Experimental Approach

Abstract: The role of intramolecular hydrogen bonding (HB) on the bond-dissociation enthalpy (BDE) of the phenolic O-H and on the kinetics of H-atom transfer to peroxyl radicals (k(inh)) of several 2-alkoxyphenols was experimentally quantified by the EPR equilibration technique and by inhibited autoxidation studies. These compounds can be regarded as useful models for studying the H-atom abstraction from 2-OR phenols, such as many lignans, reduced coenzyme Q and curcumin. The effects of the various substituents on the B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 52 publications
(131 reference statements)
2
41
0
Order By: Relevance
“…The logarithms of the rate constants for H-atom abstraction are known to be inversely proportional to the BDE(O-H)s. The slope and the y-intercept of these plots are dependent on the nature of the abstracting radicals and on the steric crowding around the phenolic OH group, respectively. [30,32,33] In Figure 5 it is shown that 5b-d are on the same line of unhindered phenols, this being consistent with the presence, in ortho position to the OH group, of only one methyl group in 5b,c and with the absence of any substituent in 5d. Compound 5a is near to the line of 2,6-dimethylphenols, as expected from its structure.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The logarithms of the rate constants for H-atom abstraction are known to be inversely proportional to the BDE(O-H)s. The slope and the y-intercept of these plots are dependent on the nature of the abstracting radicals and on the steric crowding around the phenolic OH group, respectively. [30,32,33] In Figure 5 it is shown that 5b-d are on the same line of unhindered phenols, this being consistent with the presence, in ortho position to the OH group, of only one methyl group in 5b,c and with the absence of any substituent in 5d. Compound 5a is near to the line of 2,6-dimethylphenols, as expected from its structure.…”
Section: Resultssupporting
confidence: 82%
“…Compound 5a is near to the line of 2,6-dimethylphenols, as expected from its structure. [33] Similarly to natural derivatives, the antioxidant activity of 4-thiatocopherols increases with the number of methyl groups on the aromatic ring. α-4-Thiatocopherol 5a has the lowest BDE(O-H) and is the most active antioxidant (highest k inh ) of the compounds prepared ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Since such intramolecular H bonds have a strength on the order of ∼3 kcal mol −1 , they significantly influence the reactivity of these compounds in apolar solvents. 118 Organochalcogen substituents, besides participating intramolecular H bonding when they are ortho to the -OH, have generally quite complex stereoelectronic properties, as they behave as EW groups in the phenol and as ED groups in the phenoxyl radical, upon rotation with respect to the ring skeleton. A detailed discussion on their stereoelectronic properties and effect on BDE OH and reactivity has been provided.…”
Section: Methodsmentioning
confidence: 99%
“…The actual mechanism by which the curcumin works as an antioxidant is still unclear. However, some studies attributed this effect to curcumin content of phenolic hydroxyl groups [27], β-diketone [28], and ortho-alkoxy group [29] in addition to its ability to interact with the thiol group of glutathione and thioredoxin1 [30]. Fu and his group had studied the effect of …”
Section: Discussionmentioning
confidence: 99%